Factors that determine aneurysm occlusion after embolization with the Woven EndoBridge (WEB). (24th October 2018) - Kabbasch, Christoph; Goertz, Lukas; Siebert, Eberhard; Herzberg, Moriz; Borggrefe, Jan; Dorn, Franziska; Liebig, Thomas
Abstract : Background: The Woven EndoBridge (WEB) device is a novel endovascular tool for the treatment of wide-necked intracranial aneurysms. Objective: To evaluate factors influencing aneurysm occlusion and aneurysm recurrence after WEB embolization. Methods: A total of 113 patients (mean age 58.9±11.9 years) with 114 aneurysms (mean size 8.6±4.6 mm) were successfully treated with the WEB device at three German tertiary care centers between May 2011 and February 2018. Aneurysm occlusion was evaluated using the Raymond-Roy occlusion classification. We retrospectively collected patient characteristics, anatomical details, and procedural aspects and evaluated their impact on aneurysm occlusion and recurrence. Results: Of 98 patients available for a 6-month angiographic follow-up, complete occlusion was achieved in 62.2%, neck remnants in 21.4%, and aneurysm remnants in 16.3%. Aneurysm recurrence occurred in 15.3%. Initial partial aneurysm thrombosis, recurrent aneurysms, aneurysm size, and simultaneous treatment by WEB and coil were associated with aneurysm remnants (p<0.05). Initial partial aneurysm thrombosis, increasing aneurysm size, and treatment by WEB and coil also predicted aneurysm recurrence (p<0.05). In the subgroup analysis of 71 aneurysms treated with WEB only, initial incomplete occlusion and male sex were associated with aneurysm remnants (p<0.05), while aneurysm height correlated with aneurysm recurrence (p=0.008). Conclusions: The WEB provides a high rate of adequate occlusion even in a subset of complex wide-necked intracranial aneurysms. Anatomic results tend to be less favourable in large and partially thrombosed aneurysms and after treatment with WEB and coil.